An Overview on the Therapeutic Function of Foods Enriched with Plant Sterols in Diabetes Management - Selvaraj Jayaraman; Anitha Roy; Srinivasan Vengadassalapathy; Ramya Sekar; Vishnu Priya Veeraraghavan; Ponnulakshmi Rajagopal; Gayathri Rengasamy; Raktim Mukherjee; Durairaj Sekar; Reji Manjunathan (MDPI AG, 2021)
Diabetes is one of the most significant health issues across the world. People identified with diabetes are more vulnerable to various infections and are at a greater risk of developing cardiovascular diseases. The plant-based food we consume often contains many sterol-based bioactive compounds. It is well documented that these compounds could effectively manage the processes of insulin metabolism and cholesterol regulation. Insulin resistance followed by hyperglycemia often results in oxidative stress level enhancement and increased reactive oxygen species production. At the molecular level, these changes induce apoptosis in pancreatic cells and hence lead to insulin insufficiency. Studies have proved that plant sterols can lower inflammatory and oxidative stress damage connected with DNA repair mechanisms. The effective forms of phyto compounds are polyphenols, terpenoids, and thiols abundant in vegetables, fruits, nuts, and seeds. The available conventional drug-based therapies for the prevention and management of diabetes are time-consuming, costly, and with life-threatening side effects. Thereby, the therapeutic management of diabetes with plant sterols available in our daily diet is highly welcome as there are no side effects. This review intends to offer an overview of the present scenario of the anti-diabetic compounds from food ingredients towards the therapeutic beneficial against diabetes.